Educar sem corrimões? A formação em tempos de ruptura com a tradição - Ludwig, Cristiane (2013)
This dissertation seeks to understand Hannah Arendt thought as hermeneutical link of formation comprehension, in face to the situation of breaking with tradition. Taking, as background, the turnaround operations of the category framework from the tradition, that destabilize the strict underpinnings of the thought, producing a crisis in education, it is brought the idea of the activity of thinking by dis-sensorialization as a hermeneutical resource in pedagogical field. This act implies in taking into account the real experience, but does not submitted to it at all; otherwise, there will not activity of the thought. This last occurs by experience contact and, at the same time, disengagement. Nevertheless, in order to have dis-sensorialization, it is necessary the pedagogical invention of telling stories, for example. For that, it is sought to recover some reflections from her work A Vida do Espírito, focusing on the understanding of the proposal of conservation as education essence, in light of the metaphor of the thought without handrails. Under this condition, it is asked: how the Hannah Arendt perspective of the thought worried about past conservation can yet give stimulus to the contemporary formation? Beyond the cognitive sphere of the senses directed to know , the idea of the activity of thinking helps in the resizing of education meaning to a more comprehensive place. Such condition also replaces the dichotomies of pedagogical theories, divided, historically, between the attraction from the new education and the coming back of the tradition. In this sense, the teacher formation, beyond be conducted by the authority to assure the discipline or the students interests, receives orientation from both positions, bringing thus, new comprehensive possibilities. Turning present what is in absence to the senses and the experiences, the activity of thinking by dis-sensorialization makes arise, under language perspective, the stranger gaze and voice so precious to formative processes , at the storyteller image, that invites his hearers to reflect, making each one takes a decision and begin something new. Despite of the breaking with the tradition, the inspiration in the youngsters birth and in the commitment with the amor mundi lead the education to go away from the confines of dichotomies and modes, caused by not listen to his voice, due to its fall. The capacity of creating possibilities by the youngsters birth and the amor mundi (re)kindle the dialogue between Philosophy and Education at the horizon common to everybody.